Moving Beyond the Millennium Development Goal for Water: Testing the Safety and Sustainability of Drinking Water Solutions in Honduras & El Salvador - Kayser, Georgia. (2017)
Abstract: Diarrheal disease is responsible for 2.2 million deaths, of which 1.5 million are of children under five; and inadequate access to drinking water is a major cause of these deaths. Providing households with piped drinking water is often considered the gold standard approach for reducing diarrheal disease, and is an aim of the Millennium Development Goal (MDG) for water. Unfortunately, even piped drinking water systems often provide unreliable water of poor quality, and in insufficient quantity to protect households from disease. This is especially true for rural community-run drinking water systems in developing countries. Identifying technological and programmatic innovations that protect households better from water-borne disease at low cost would thus be of great value. This dissertation measures the water quality, health and sustainability impacts of three interventions that might reduce the global burden of water-borne disease and documents the shortcomings of the MDG for water. In Paper I, using a case-control design, qualitative and quantitative methods, and matched pair analysis, it first examines the performance of the Circuit Rider (CR) model in 60 communities in El Salvador. The CR model provides technical, financial, and operational assistance to community-run rural water systems. The results establish that CR communities enjoyed significantly better microbiological water quality, enhanced financial management and transparency, and greater investment in water treatment and system maintenance. Paper II examines the impacts and cost of distributing household-level water filters and safe storage units (HWFS) relative to community-level treatment systems (CTS) for use with low quality piped drinking water, using a quasi-randomized trial involving 334 households (135 HWF, 62 CTS, and 137control) over one-year in Honduras. HWFS and CTS households had significantly improved microbiological water quality, and 61% of HWFSs and 46% of CTSs were still in use after one year. In Paper III, data collected over two years for the HWFS and control households reveal that 47% of the filters were still in use and continued to provide households with water of significantly higher quality. In sum, the CR model, HWFS and CTS are all associated with significantly improved water quality, are low-cost drinking water interventions (cost per person per year is $.20 CR model, $3.63 for the HWF and $1.37 for the CTS), and could be utilized to reduce the global disease burden.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: William Moomaw.; Committee: Jeffrey Griffiths, Julie Schaffner, and Beatrice Rogers.; Keywords: Environmental health, Political Science, and Water resources management.